Near-real-time GIS database updating system using GPS and telecommunication technologies - Omar, Abdullah Hisam (2005)
The need for real-time data acquisition and maintaining process in Geographic Information System(GIS) technology was one of important aspect to ensure that there will be no double dipping of data, a very fast an accurate field data collecting and significantly help to save time and cost in maintaining GIS database. Apart from that, an off-site manager or decision makers can make rapid evaluation of progress and preliminary results while maintaining GIS database. The method of gathering field data in maintaining GIS database typically a time-consuming task due to the need for measurement and attributes of data often in remote regions. To be worthwhile a very fast and accurate field data collecting system that significantly help to save time and cost in updating GIS database should be develop to allowing the GIS field data being transmit in real-time to headquarters. The recent advance in mobile information technology and wireless data communications have created opportunities for developing tools that bring computing power to field worker. Based on available coverage in the region, an integration of Global Positioning System Bluetooth receiver, Personal Digital Assistant and General Packet Radio Service enable mobile phone will be used for enable real-time streaming of field data by Short Message Service (SMS), Email or Internet. Wireless transmission of the data contents is periodically made to an Email Server where it is will transfer the data into off-site manager database at headquarters. The field data then will be process and automatically updating the GIS database.